Questioning practice in EFL classrrom interactions: from type to syntactical form - Hieronimus Canggung Darong (International Journal of Education and Learning, 2021)
As the most prominent features uttered by EFL teachers in classroom interactions, questioning plays important roles to invite student responses. This study was an attempt to analyse questioning practice employed by EFL teachers in terms of ways or strategies namely contingency, convergence-divergence, and syntactical form in their interactions with students. Data were gathered from four purposefully chosen English teachers’ questions employed during their interactions with students at a larger corpus project of UMSpEAKs (Universitas Negeri Malang Spoken English in Academic Kontexts), thus, transcribed and analysed following the principle of Conversation Analysis (CA). The Conversation Analysis revealed that the contingent questions differently appeared for each teacher. The most question type used to be contingent was a clarification. Besides, the teacher questions were mainly convergent and divergent by means of display questions that consistently evolved student contributions and enlarge the talks. Meanwhile, the most frequently occurring question- syntactical form was W-h questions and followed by yes-no question forms. The W-h questions having more syntactically complex utterances than yes/no questions were powerful and would prompt more students’ responses. Meanwhile, yes/no questions were posed when the teachers felt that students have difficulty in answering or understanding the W-h and how/what about questions and invited short responses. Thus, contingency, convergence-divergence, and syntactical form that was differently constructed following the commodity exchange in the classroom discourse were very beneficial to invite student responses, discursively carry functions, and extend the classroom discourse.